Composite polymer electrolyte based on surface organic modified lithium titanium aluminum phosphate as well as preparation method and application of composite polymer electrolyte
The reaction of surface organically modified lithium titanium aluminum phosphate with polymer monomer and silane coupling agent is carried out to form a composite polymer electrolyte, which solves the problem of insufficient stability of LATP in lithium-ion batteries, and achieves the effect of high room temperature conductivity and wide electrochemical stability window.
Patent Information
- Application Number
- CN202510369464.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
AI Technical Summary
The stability of titanium aluminum lithium phosphate (LATP) when in contact with lithium metal is poor, resulting in unstable electrolytes and shortening the cycle life of lithium-ion batteries.
The surface organically modified titanium aluminum phosphate is used to form a composite polymer electrolyte by reacting with polymer monomer and silane coupling agent, thereby improving the dispersion and interface stability of LATP.
The room temperature conductivity and electrochemical stability window of composite polymer electrolytes are improved, and the transmission continuity of lithium ions and the cycle life of the battery are enhanced.
Smart Images

Figure CN119875141A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate and a preparation method and application thereof. Background Art
[0002] Lithium aluminum titanium phosphate (LATP) has been studied in depth as a NASICON-type lithium-ion fast conductor. It has excellent room temperature ion conductivity, advantages in preparation cost, and good air stability. Therefore, it is regarded as one of the most promising solid electrolytes for large-scale mass production. However, the stability of this material when in contact with lithium metal is poor. During the charge and discharge cycle, Ti 4+ Easily reduced to Ti 3+ This phenomenon will cause electrolyte instability, thereby shortening the cycle life of the battery, greatly limiting its application prospects in the field of lithium-ion batteries.
[0003] The preparation of composite electrolytes by blending polymers with LATP can reduce the redox reaction of LATP during charging and discharging and improve battery life. However, in traditional composite solid electrolytes prepared by blending, ceramic particles and polymers are only connected by physical action, and the reliability is low. In addition, there are interface problems between polymers and ceramic particles, the resistance is large, and lithium ions are difficult to conduct at the polymer-ceramic interface. Not only that, considering the size effect of fillers in composite electrolytes, LATP powder usually requires a smaller particle size, but a smaller particle size brings a larger surface energy, which makes the powder easy to agglomerate during the mixing process. The poor dispersibility of LATP powder will lead to uneven interface potential, which can easily lead to the growth of lithium dendrites. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate and its preparation method and application. The room temperature conductivity of the composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate is 1.2×10 -5 ~6.3×10 -3 S cm -1 , the electrochemical stability window is 4.3~5.7V.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate, comprising the following steps:
[0007] In an inert atmosphere, polymer monomers, lithium salts, organic solvents and lithium aluminum titanium phosphate modified by a silane coupling agent are mixed, cross-linked and cured to obtain the composite polymer electrolyte based on the surface organically modified lithium aluminum titanium phosphate;
[0008] The polymer monomer is 1,3-dioxolane (DOL);
[0009] The silane coupling agent in the silane coupling agent-modified lithium aluminum titanium phosphate is an epoxy silane coupling agent.
[0010] Optionally, the inert atmosphere includes a nitrogen atmosphere or an argon atmosphere.
[0011] Preferably, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate and lithium bistrifluoromethanesulfonyl imide.
[0012] Preferably, the polymer monomer and the lithium salt are added in a ratio of lithium oxygen ratio EO:Li=8:1~16:1; the addition amount of the silane coupling agent modified lithium aluminum titanium phosphate is 5~40% of the mass of the composite polymer electrolyte based on surface organic modified lithium aluminum titanium phosphate.
[0013] Preferably, the organic solvent comprises tetrahydrofuran, dichloromethane, chloroform, acetonitrile, propylene carbonate, toluene, dioxane, N,N-dimethylformamide or ethylene glycol dimethyl ether.
[0014] Preferably, the amount of the organic solvent added is 25-40% of the mass of the polymer monomer.
[0015] Preferably, the epoxy silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane (KH560) or γ-glycidyloxypropyltriethoxysilane (SI561).
[0016] The method of modifying lithium aluminum titanium phosphate with a silane coupling agent in the present invention can be a general method of modifying inorganic materials with a silane coupling agent.
[0017] Preferably, the cross-linking curing temperature is 25-80° C. and the time is 0.5-6 h.
[0018] The second technical solution of the present invention is to provide a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate prepared according to the preparation method of the composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate.
[0019] The third technical solution of the present invention is to provide an application of the above-mentioned composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate in solid electrolyte.
[0020] The fourth technical solution of the present invention is to provide an application of the above-mentioned composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate in lithium ion batteries.
[0021] The beneficial technical effects of the present invention are as follows:
[0022] The present invention utilizes the dispersed reaction sites in the polymer chain to react with the surface groups of the modified LATP, so that the modified LATP particles are evenly dispersed along the polymer chain to form a compact network structure. The modified LATP and the polymer are tightly connected by chemical bonds, which improves the discontinuous lithium ion transmission caused by the poor contact between the organic-inorganic interface of the traditional composite electrolyte. The introduction of LATP makes the electrolyte have good mechanical properties and thermal stability. The composite polymer electrolyte has good interface stability, a wide electrochemical window (>4.3V), high room temperature ionic conductivity (>10 -5 S cm -1 ).
[0023] The composite polymer electrolyte of the invention has a simple preparation process and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the synthesis of a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate according to Example 1 of the present invention. DETAILED DESCRIPTION
[0025] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0026] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.
[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0030] Example 1
[0031] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0032] (1) Anhydrous ethanol (10 mL) and LATP (1.905 g) were pre-mixed to form a uniform LATP dispersion. Separately, silane coupling agent KH560 (0.09 mL, 0.095 g) was mixed with anhydrous ethanol (2.24 mL, 1.767 g), deionized water (0.038 mL, 0.038 g) was added, and the pH value of the solution was adjusted to 5 with acetic acid to promote the hydrolysis of KH560. The mixed solution was ultrasonically treated for 1 h to obtain a KH560 solution with a mass fraction of 5%. Subsequently, the KH560 solution was added to the LATP dispersion, stirred at 50 °C for 12 h, centrifuged, washed with anhydrous ethanol, repeated three times, and dried at 60 °C in a vacuum to obtain a white powder with a silane coupling agent-modified LATP (KH560@LATP) with a coverage of 5%.
[0033] (2) In an argon-filled glove box, DOL (4.01 mL, 4.246 g), lithium difluorooxalatoborate (2.480 g), organic solvent ethylene glycol dimethyl ether (DME) (1.47 mL, 1.274 g) and KH560@LATP (2 g) powder were mixed and directly assembled into a button cell, where the lithium-oxygen ratio of DOL to lithium difluorooxalatoborate was EO:Li=8:1. Since lithium difluorooxalatoborate (LiDFOB) can act as an initiator to catalyze the cation-induced ring-opening polymerization of cyclic alcohols, the overall mixture undergoes an in-situ polymerization reaction; the added DME can promote the dissociation of lithium salts and the transfer of lithium ions. Heating at 60°C for 1h allowed the polymer monomer to fully react with the surface groups of the modified LATP. The electrolyte was disassembled and observed to obtain a white and smooth block-shaped composite polymer electrolyte (PDOL-KH560@LATP), with KH560@LATP accounting for 20% of the mass of PDOL-KH560@LATP.
[0034] The schematic diagram of synthesizing the composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate according to Example 1 of the present invention is shown in Figure 1 .
[0035] Example 2
[0036] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0037] The difference from Example 1 is that the silane coupling agent used is γ-glycidyloxypropyltriethoxysilane (SI561), the modified LATP obtained is SI561@LATP, and the composite polymer electrolyte PDOL-SI561@LATP is obtained. The other implementation conditions are the same as those in Example 1.
[0038] Example 3
[0039] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0040] The difference from Example 2 is that the lithium salt used is lithium tetrafluoroborate (LiBF4), EO:Li=8:1, and the composite polymer electrolyte PDOL-SI561@LATP is prepared. The other implementation conditions are the same as those in Example 2.
[0041] Example 4
[0042] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0043] The difference from Example 2 is that the lithium salt used is lithium hexafluorophosphate (LiPF6), EO:Li=8:1, and the composite polymer electrolyte PDOL-SI561@LATP is prepared. The other implementation conditions are the same as those in Example 2.
[0044] The performance of the composite polymer electrolytes prepared in Examples 1-4 was characterized, and the test results are shown in Table 1.
[0045] Table 1 Properties of the composite polymer electrolytes prepared in Examples 1-4
[0046] Example Average thickness(mm) <![CDATA[Ionic conductivity (S·cm -1 , 25 °C)]]> Electrochemical stability window (V) 1 0.032 <![CDATA[1.576×10 -4 ]]> 5.01 2 0.034 <![CDATA[1.431×10 -4 ]]> 5.09 3 0.033 <![CDATA[1.513×10 -4 ]]> 5.15 4 0.038 <![CDATA[0.231×10 -4 ]]> 4.69
[0047] As can be seen from Table 1, the length of the alkyl group in the silane coupling agent will affect the degree of crosslinking with the polymer, effectively improve the internal structure of the solid electrolyte, and then react in the ionic conductivity and electrochemical window. In addition, when the types of lithium salts are different, since the lithium salts in Example 3 and Example 2 have similar action mechanisms, both use Lewis acid and base to strengthen the binding bond energy, and thus have high lithium ion transmission efficiency, while the lithium salt action mechanism of Example 4 is simply an initiator action, which is worse than Examples 2 and 3.
[0048] Example 5
[0049] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0050] The difference from Example 1 is that the organic solvent used is acetonitrile (ACN) (1.47 mL, 1.16 g), and the other implementation conditions are the same as those in Example 1.
[0051] Example 6
[0052] The difference from Example 1 is that the organic solvent used is propylene carbonate (PC) (1.47 mL, 1.76 g), and the other implementation conditions are the same as those in Example 1.
[0053] Example 7
[0054] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0055] The difference from Example 1 is that the organic solvent used is tetrahydrofuran (1.47 mL, 1.31 g), and the other implementation conditions are the same as those of Example 1.
[0056] The performance of the composite polymer electrolytes prepared in Examples 5-7 was characterized, and the test results are shown in Table 2.
[0057] Table 2 Properties of the composite polymer electrolytes prepared in Examples 5-7
[0058] Example Average thickness(mm) <![CDATA[Ionic conductivity (S·cm -1 , 25 °C)]]> Electrochemical stability window (V) 5 0.032 <![CDATA[1.341×10 -4 ]]> 5.02 6 0.032 <![CDATA[1.213×10 -4 ]]> 4.75 7 0.032 <![CDATA[1.431×10 -4 ]]> 5.11
[0059] As shown in Table 2, the above organic solvents can successfully prepare composite electrolytes and are well dispersed in each solution. Example 5 can effectively dissociate lithium salts, thereby improving electrochemical performance to obtain high ionic conductivity and a wide electrochemical stability window, that is, improving the dielectric constant. Example 6 can form a stable electrolyte and strengthen the electrochemical stability window. Example 7 is the same as Example 1 in that it forms a complex, strengthens structural stability, and improves ionic conductivity.
[0060] Example 8
[0061] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0062] The difference from Example 1 is that acetic acid is added to adjust the pH value to 4.5, and the other implementation conditions are the same as those of Example 1.
[0063] Example 9
[0064] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0065] The difference from Example 1 is that the mass concentration of the KH560 solution used is 2%, and the other implementation conditions are the same as those of Example 1.
[0066] Example 10
[0067] Preparation of composite polymer electrolyte based on surface organically modified lithium aluminum titanium phosphate:
[0068] The difference from Example 1 is that the ultrasonic time of the KH560 solution is adjusted to 5 minutes (ie, the hydrolysis time), and the other implementation conditions are the same as those in Example 1.
[0069] The performance of the composite polymer electrolytes prepared in Examples 8-10 was characterized, and the test results are shown in Table 3.
[0070] Table 3 Properties of the composite polymer electrolytes prepared in Examples 8-10
[0071] Example Average thickness(mm) <![CDATA[Ionic conductivity (S·cm -1 , 25 °C)]]> Electrochemical stability window (V) 8 0.032 <![CDATA[1.551×10 -4 ]]> 5.02 9 0.032 <![CDATA[1.013×10 -4 ]]> 4.86 10 0.032 <![CDATA[0.931×10 -4 ]]> 4.61
[0072] As can be seen from Table 3, the hydrolysis process of the silane coupling agent is the most important pre-treatment for the condensation reaction of the silane coupling agent. The hydrolysis process needs to grasp the hydrolysis time, solution pH, and final concentration. If the concentration of the silane coupling agent is not enough, such as Example 9, the overall effect is weak, and the improvement of the solid electrolyte is low. If the hydrolysis time is too fast, such as Example 10, the silane coupling agent is unstable before the subsequent experiment begins, the ionic conductivity of the overall solid electrolyte is low, and the electrochemical stability window is poor.
[0073] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate, characterized in that: The following steps are involved: In an inert atmosphere, polymer monomers, lithium salts, organic solvents and lithium aluminum titanium phosphate modified by a silane coupling agent are mixed, cross-linked and cured to obtain the composite polymer electrolyte based on the surface organically modified lithium aluminum titanium phosphate; The polymer monomer is 1,3-dioxolane; The silane coupling agent in the silane coupling agent-modified lithium aluminum titanium phosphate is an epoxy silane coupling agent.
2. The preparation method according to claim 1, characterized in that: The lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate and lithium bistrifluoromethanesulfonyl imide.
3. The preparation method according to claim 1, characterized in that: The polymer monomer and the lithium salt are added in a ratio of lithium oxygen EO:Li=8:1~16:1; the addition amount of the silane coupling agent modified lithium aluminum titanium phosphate is 5~40% of the mass of the composite polymer electrolyte based on surface organic modified lithium aluminum titanium phosphate.
4. The preparation method according to claim 1, characterized in that: The organic solvent includes tetrahydrofuran, dichloromethane, chloroform, acetonitrile, propylene carbonate, toluene, dioxane, N,N-dimethylformamide or ethylene glycol dimethyl ether.
5. The preparation method according to claim 1, characterized in that: The amount of the organic solvent added is 25-40% of the mass of the polymer monomer.
6. The preparation method according to claim 1, characterized in that: The epoxy silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane or γ-glycidyloxypropyltriethoxysilane.
7. The preparation method according to claim 1, characterized in that: The cross-linking curing temperature is 25-80° C. and the time is 0.5-6 hours.
8. A composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate prepared according to the preparation method of a composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate according to any one of claims 1 to 7.
9. Use of the composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate according to claim 8 in solid electrolytes.
10. Use of the composite polymer electrolyte based on surface organically modified lithium titanium aluminum phosphate according to claim 8 in a lithium ion battery.
Citation Information
Patent Citations
Modified composite solid electrolyte and preparation method thereof
CN113725482A
Modified inorganic electrolyte, composite solid electrolyte and application thereof
CN118380639A
Preparation method of polymer gel electrolyte
CN118553996A
Three-dimensional cross-linked gel polymer electrolyte as well as preparation method and application thereof
CN118970164A
Cited By
Composite electrolyte material with lithium aluminum germanium phosphate core coated with metal organic framework shell layer and application of composite electrolyte material
CN122051398A